POLIGAMI DALAM KURUN WAKTU SATU HARI DITINJAU DARI UNDANG-UNDANG PERKAWINAN DAN HUKUM ISLAM - Amri Wahyudi (Muqaranah, 2021)
Abstract In today's era the spread of information is very fast and wide, we can get information about events that occur in other parts of the world in Indonesia so quickly, this is the impact of advances in technology and information. Recently, we were shocked by the news about the marriage of a man with two women at the same time in Saling sub-district, Empat Lawang district, South Sumatra district. Judging from Law No. 1 of 1974 concerning marriage, of course polygamy in a period of less than one week is carried out, because there are conditions that polygamy must obtain permission from the Court, while the process to obtain such a permit would take a long time so it can be ascertained that polygamy that is carried out within one day cannot be done and if it is done then the polygamy is not recorded or illegal. Whereas in Islamic law polygamy can be done within one day and is valid with a record of the pillars and the conditions are met. Keywords: Polygamy, Marriage, Islamic Law